Changes in the localization of the rat canalicular conjugate export pump mrp2 in phalloidin‐induced cholestasis - Rost, Daniel; Kartenbeck, Jürgen; Keppler, Dietrich (Hepatology, 2003)
Administration of phalloidin, one of the toxic peptides of the mushroom Amanita phalloides, leads to rapid and sustained cholestasis in rats. Although attributed to the interaction of phalloidin with microfilaments, the events leading to cholestasis are incompletely understood.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 23.02.2021